Selwynia, a senior synonym of Aphanodactylus, with a redescription of Selwynia laevis (Crustacea: Brachyura: Pinnotheroidea: Aphanodactylidae). (8th October 2014) - Ng, Peter K.L.; Clark, Paul F.
Abstract : Selwynia, is regarded as a senior subjective synonym of Aphanodactylus (Crustacea: Brachyura: Pinnotheroidea: Aphanodactylidae). This synonymy does not affect the family name Aphanodactylidae. A diagnosis is provided for Selwynia laevis and this species is re-described.